Persistent Exposure to Porphyromonas gingivalis Promotes Proliferative and Invasion Capabilities, and Tumorigenic Properties of Human Immortalized Oral Epithelial Cells - Geng, Fengxue; Liu, Junchao; Guo, Yan; Li, Chen; Wang, Hongyang; Wang, Hongyan; Zhao, Haijiao; Pan, Yaping (Frontiers in Cellular and Infection Microbiology, 2017)
Recent epidemiological studies revealed a significant association between oral squamous cell carcinoma (OSCC) and Porphyromonas gingivalis, a major pathogen of periodontal disease. As a keystone pathogen of periodontitis, P. gingivalis is known not only to damage local periodontal tissues, but also to evade the host immune system and eventually affect systemic health. However, its role in OSCC has yet to be defined. To explore the underlying effect of chronic P. gingivalis infection on OSCC and to identify relevant biomarkers as promising targets for therapy and prevention, we established a novel model by exposing human immortalized oral epithelial cells (HIOECs) to P. gingivalis at a low multiplicity of infection for 5 to 23 weeks. The P. gingivalis infected HIOECs were monitored for tumor biological alteration by proliferation, wound healing, transwell invasion and gelatin zymography assays. Microarray and proteomic analyses were performed on HIOECs infected with P. gingivalis for 15 weeks, and some selected data were validated by quantitative real-time PCR and (or) western blot on cells infected for 15 and 23 weeks. Persistent exposure to P. gingivalis caused cell morphological changes, increased proliferation ability with higher S phase fraction in the cell cycle, and promoted cell migratory and invasive properties. In combining results of bioinformatics analyses and validation assays, tumor-related genes such as NNMT, FLI1, GAS6, lncRNA CCAT1, PDCD1LG2, and CD274 may be considered as the key regulators in tumor-like transformation in response to long-time exposure of P. gingivalis. In addition, some useful clinical biomarkers and novel proteins were also presented. In conclusion, P. gingivalis could promote tumorigenic properties of HIOECs, indicating that chronic P. gingivalis infection may be considered as a potential risk factor for oral cancer. The key regulators detected from the present model might be used in monitoring the development of OSCC with chronic periodontal infection.